Pengaruh Kualitas Produk dan Harga Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan sebagai Variabel Mediasi - Rhi Muhammad Ibnu Hibban; Osly Usman (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the effect of product quality and price on customer loyalty through customer satisfaction as a mediating variable. The research employed a quantitative approach using an explanatory research design. The population consisted of customers who had purchased or used the products under study, with a sample of 200 respondents selected using a purposive sampling technique. Data were collected through a structured questionnaire using a five-point Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4 software. The results indicate that product quality has a positive and significant effect on customer satisfaction (β = 0.336; p < 0.001) and customer loyalty (β = 0.253; p < 0.001). Price also has a positive and significant effect on customer satisfaction (β = 0.336; p < 0.001) and customer loyalty (β = 0.206; p = 0.002). Furthermore, customer satisfaction has a positive and significant effect on customer loyalty (β = 0.298; p < 0.001). The mediation analysis reveals that customer satisfaction partially mediates the relationship between product quality and customer loyalty (β = 0.100; p = 0.001), as well as the relationship between price and customer loyalty (β = 0.100; p = 0.001). These findings indicate that improving product quality and implementing appropriate pricing strategies not only enhance customer loyalty directly but also indirectly through increased customer satisfaction. The findings suggest that companies should prioritize continuous improvements in product quality and establish competitive pricing strategies that reflect the value perceived by customers in order to enhance customer satisfaction and foster long-term customer loyalty.